Effect of four rearing substrates on the yield and the chemical composition of housefly larvae, Musca domestica L. 1758 (Diptera: Muscidae) - GANDA, Haffizou; ZANNOU, Elisabeth Tohouédé; KENIS, Marc; ABIHONA, Aristide Hermann; HOUNDONOUGBO, Parfait; CHRYSOSTOME, CHRISTOPHE ACHILLE A. MAHUSSI; MENSAH, JEAN-BAPTISTE (My University, 2021)
The use of insects such as black soldier fly (Hermetia illucens) and common housefly (Musca domestica) as an alternative source of protein in animal feed has gained interest in recent years. This study investigated the effect of four growing substrates on the biomass, crude nutrient and mineral composition of M. domestica larvae. After a 5-day growing period, the total dry matter (DM) of maggot yield was 69.70; 59.33; 43.58 and 41.04 g/kg for soybean bran + maize pericarp, pig manure, maize bran and chicken manure, respectively. The chemical composition of maggot was significantly influenced by the type of substrate. The highest contents in crude ash (124.90 g/kg DM), crude fibre (167.65 g/kg DM) and sodium (53.47 g/kg DM) were obtained from maggots produced with pig manure. Maggots produced with the mixture of soybean bran and maize pericarp showed the highest fat (218.40 g/kg DM), crude protein (517.10 g/kg DM), potassium (89.05 g/kg DM) and metabolizable energy (4198.52 kcal/kg DM) contents. Maggots from maize bran had more calcium (51.84 g/kg DM) and phosphorus (104.55 g/kg DM) than those from others substrates. This study showed that soybean bran + maize pericarp and pig manure are the most suitable substrates for maggots’ production to provide high yields of larvae with a good nutrient content.
Keywords: Animal feed · Maggot yield · Musca domestica · Nutrients content · Protein